Peran Pondok Pesantren Mahfudiyatul Islamiyah Terhadap Kualitas Keagamaan Masyarakat Karasak - Apap Ahmad Qusyaeri; Syamsuddin RS; Dedi Herdiana (Tamkin: Jurnal Pengembangan Masyarakat Islam, 2022)
This study aims to analyze the role of the Mahfidiyatul Islmaiyah Islamic boarding school on the religious quality of society. The Islamic religious rituals of the community after the existence of the Islamic Boarding School, as well as the social and Islamic aspects of the community after the Islamic Boarding School. The method used in this research is descriptive with a qualitative approach to describe the conditions and situations or various social reality phenomena that exist in the community which are the object of research. Data collection was done by means of observation, interviews, documentation.The results showed that the Mahfidiyatul Islmaiyah Islamic boarding school provided various religious roles for the community. There is an increase in religious rituals such as prayer, fasting, zakat, the number of recitations, an increase in the reading and writing of the al-quran and to social aspects which all lead to positive changes.